A quantum crystallographic protocol for general use - Yaser Balmohammadi; Lorraine A. Malaspina; Yuiga Nakamura; Georgia Cametti; Milosz Siczek; Simon Grabowsky (Scientific Reports)
Abstract Quantum crystallography has become ever more important in recent years for the accurate determination of molecular and crystal structures. The results of quantum crystallographic refinements of X-ray data are as accurate and precise as from neutron diffraction and they give access to the complete electronic structure of the compound under investigation. Is the method now mature enough and easy enough to use to extend and ultimately supersede standard X-ray crystal structure determination routines? We utilize the world’s most common crystal structure—the YLID test crystal that every owner of an X-ray diffractometer receives with their machine—to show under which circumstances routine, low-resolution, and even room-temperature measurements can be subjected to quantum crystallographic refinement. Based on this, we describe a quantum crystallographic protocol step by step that makes application of quantum crystallographic refinement easy to use and reproducible. We encourage that valuable YLID test measurements are not discarded but made available for method development, increasing the availability of repeated measurements from a handful to tens of thousands.